Multifunctional Scaffolds for Assembling Cancer-Targeting Immune Stimulators Using Chemoselective Ligations - Conibear, Anne C.; Thewes, Karine; Groysbeck, Nadja; Becker, Christian F. W. (Frontiers in Chemistry, 2019)
Chemoselective ligations allow chemical biologists to functionalise proteins and peptides for biomedical applications and to probe biological processes. Coupled with solid phase peptide synthesis, chemoselective ligations enable not only the design of homogeneous proteins and peptides with desired natural and unnatural modifications in site-specific locations but also the design of new peptide and protein topologies. Although several well-established ligations are available, each method has its own advantages and disadvantages and they are seldom used in combination. Here we have applied copper-catalysed azide-alkyne ‘click’, oxime, maleimide and native chemical ligations to develop a modular synthesis of branched peptide and polymer constructs that act as cancer-targeting immune system engagers (ISErs) and functionalised them for detection in biological systems. We also note some potential advantages and pitfalls of these chemoselective ligations to consider when designing orthogonal ligation strategies. The modular synthesis and functionalisation of ISErs facilitates optimisation of their activity and mechanism of action as potential cancer immunotherapies.